Exploring the influence of pet ownership on the mental health and well-being of at-risk children and youth in rural KwaZulu-Natal, South Africa - Hancke, Petri (Stellenbosch : Stellenbosch University, 2026)
Thesis (MA)--Stellenbosch University, 2026.